Experimental composites of polyacrilonitrile-electrospun nanofibers containing nanocrystal cellulose. Issue 11 (November 2019) - Peres, Bernardo U.; Manso, Adriana P.; Carvalho, Luana D.; Ko, Frank; Troczynski, Tom; Vidotti, Hugo A.; Carvalho, Ricardo M.
Highlights: Experimental nanofiber-reinforced resin composites were produced. The effects of nanocrystal cellulose addition to the nanofibers were evaluated. Mechanical properties were evaluated. A toughening effect was achieved with the addition of NCC-containing nanofibres to resin. Abstract: Objective: To test the effects of addition of polyacrilonitrile (PAN) nanofibers and nanocrystal cellulose (NCC)-containing PAN nanofibers on flexural properties of experimental dental composites. Methods: 11 wt% PAN in dimethylformamide (DMF) solution was electrospun at 17.2 kVA and 20 cm from the collector drum. NCC was added to the solution at 3 wt%. Fiber mats were produced in triplicates and tested as-spun. Strips (5 cm × 0.5 cm) were cut from the mat in an orientation parallel and perpendicular to the rotational direction of the collector drum. Tensile tests were performed and ultimate tensile strength (UTS), elastic modulus (E) and elongation at maximum stress (%) were calculated from stress/strain plots. Fiber mats were then infiltrated by resin monomers (50/50 BisGMA/TEGDMA wt%), stacked in a mold (2 × 15 × 25) and light-cured. Beams (2 × 2 × 25 mm) were cut from the slabs and tested in a universal testing machine. Data were analyzed by multiple t-test and one-way ANOVA ( α = 0.05). Results: Addition of 3% NCC resulted in higher tensile properties of the fibers. Fibers presented anisotropic behavior with higher UTS and E when tested in perpendicular orientation. The incorporation of 3% NCC–PAN nanofibers resulted in significant increase in work of fracture and flexural strength of experimental dental composite beams. Significance: NCC was found to be a suitable nanoparticle to reinforce experimental dental composites by incorporation via nanofiber. This fundamental study warrants future investigation in the use of electrospun nanofibres as a way to reinforce dental composites.